The First Free Women : Poems of The Early Buddhist Nuns - Weingast, Matty (Boulder : Shambhala Publications, 2020)
This new and captivating translation of the Therigatha (Verses of the Elder Buddhist Nuns) is a modern rendition of classic stories from the very first Buddhist nuns. Reflecting on their lives and revelations, these women wrote countless poems as they embraced their new lives as nuns. Heartwarming, enlightening, and sometimes tough in all the right ways, these poems have now been translated and adapted to reach a modern audience
Keywords: Buddhist poetry, American